360 DEGREE ENDOLASER VERSUS FOCAL ENDOLASER IN PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT REPAIR. Issue 11 (November 2022) - Mathai, Mariam; Godwin, Kristen S.; Albarracin, Julio; Levinson, Joshua; Broderick, Kevin; Melamud, Alexander
Abstract : A single-site retrospective chart review to determine the efficacy of 360-degree endolaser versus focal laser during primary vitrectomy for rhegmatogenous retinal detachment repair. Abstract : Purpose: To determine the efficacy of the 360-degree endolaser (360EL) versus focal laser during primary vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD) repair. Methods: A single-site retrospective chart review was performed on 241 patients who underwent PPV for primary RRD. Patients were assigned to two groups, PPV with 360EL (n = 183) and PPV without 360EL (n = 59). Only cases where surgeons performed 360EL on all RRDs or surgeons who never perform 360EL on RRDs were included. Results: The single surgery anatomical success rate in the 360EL group was 90.2% compared with 86.5% with focal laser ( P = 0.619). Epiretinal membrane formation in 360EL group at 1 year was 44.4% versus 37% with focal laser ( P = 0.429). Cystoid macular edema formation within 1 year of surgery was 25.8% in 360EL group versus 11.9% with focal laser ( P = 0.04). Conclusion: The use of 360EL in PPV for RRD repair does not improve single-surgery anatomical success in routine RRDs when compared with PPV with focal laser.